(untitled) (Emancipação, 2021)
Various forms of privatization in the right to education’s offer are underway. One of them involves an intense activity of civil association, normally characterized as non-profit, in the form of agreements with state entities. The purpose of this article is to analyze data from the Census of NonProfit Foundations and Associations produced by the Brazilian Institute of Geography and Statistics in partnership with the Institute of Economic and Applied Research in 2005, particularly from the subdivisions of the large area of Education Research: early childhood education, elementary and high school (basic education). We organized the data available in the census considering the regions of the country, the decades of creation of FASFIL, the number of workers, the average salary in FASFIL, among others. They were described using tables and collated with bibliographic references on educational policy. We conclude that the expansion of the number, the increase in breadth and the vertiginous growth of the FASFIL’s capacity to act integrate the development of the neoliberal project that confers new characteristics such as public-private relations in the offer of the right to education